Morphological variations of pulmonary veins draining into left atrium: A detailed cadaveric study - Prasenjit Bose; Umesh Choudhary; Pooja Singh; Barkha Singh; Royana Singh (Wolters Kluwer Medknow Publications, 2021)
Introduction: During pulmonary vein isolation ablation procedure, the knowledge of number and position of pulmonary veins with thickness of posterior wall of left atrium (LA) is of invaluable significance. The objective of the study was to determine the left atrial wall thickness (LAWT) and its relationship with number and variations of right pulmonary veins (RPVs) and left pulmonary veins (LPVs). Methodology: In an observational study, carried out in the Department of Anatomy, All India Institute of Medical Sciences, Raipur (Chhattisgarh), morphological variations of pulmonary veins among 75 formalin-fixed hearts were noted. The thickness of posterior wall of LA was measured in each specimen studied. The number of RPVs and LPVs was counted. Any sexual differences in these numbers were noted. Results: Normal anatomical description of two RPVs and two LPVs opening the LA was observed in 63 out of 75 heart specimens (84%). The posterior LAWT is ranged 1.28-1.48 mm where two RPVs and two LPVs enter LA. The remaining 12 specimens (16%) showed variation in the number of veins opening into LA ranging between 1 and 5 veins of either side. The posterior LAWT ranged between 1.01 and 2.53 mm in these 12 specimens. The mean posterior LAWT thickness with 3, 4, and 5 RPVs was 1.47, 1.94, and 2.43 mm, respectively. Conclusion: The thickness of posterior wall of LA increases as the number of RPVs increases. Twelve specimens (16%) showed variation in the number of veins opening into LA ranging between 1 and 5 veins of either side.